EPISTEMOLOGI AYAT MUTASHĀBIHĀT: Analisis Kaidah Nafiy pada Surah Āli ‘Imrān Ayat 7 - Dita Erlin Enjelina; Moh. Akib Muslim (UIN Siber Syekh Nurjati Cirebon, 2024)
This study aims to analyze the mutashābihāt verse in surah Āli ‘Imrān verse 7 through the perspective of Nafiy (negation) rules in order to understand its epistemological implications. Mutashābihāt verses, which contain implied meanings and multi-interpretations, often result in challenges to the interpretation of the holy verses of the Qur'ān. In Surah Āli ‘Imrān verse 7, Allah Swt. confirms the existence of clear verses (muḥkamāt) and vague verses (mutashābihāt), and states that Allah is the only one who knows the true meaning of the mutashābihāt verses. Using the rule of Nafiy, this study seeks to describe how the rejection or negation of certain meanings helps in understanding and interpreting mutashābihāt verses. This approach also examines how the method affects the formation of knowledge and understanding in the context of Islamic scholarship. The analysis shows that the Nafiy rule plays a significant role in maintaining the integrity and consistency of interpretation, as well as in guiding Muslims towards a deeper and more accurate understanding of divine revelation. The author hopes that this research can make a meaningful contribution to the study of Qur'anic interpretation and Islamic epistemology. Penelitian ini bertujuan untuk menganalisis ayat mutashābihāt melalui perspektif kaidah Nafiy (negasi) yang tercamtum dalam Q.S Āli ‘Imrān ayat 7 guna memahami implikasi epistemologisnya. Ayat mutashābihāt, yang mengandung makna tersirat dan multiinterpretasi, sering kali mengakibatkan tantangan terhadap penafsiran ayat-ayat suci Al-Qur’an. Dalam Q.S Āli ‘Imrān ayat 7, Allah SWT menegaskan adanya ayat-ayat yang jelas (muḥkamāt) dan ayat-ayat yang samar (mutashābihāt), serta menyatakan bahwa hanya Allah satu-satunya yang memahami makna yang sebenarnya dari ayat-ayat mutashābihāt tersebut. Dengan menggunakan kaidah Nafiy, penelitian ini berusaha menguraikan bagaimana penolakan atau negasi terhadap makna-makna tertentu membantu dalam memahami dan menafsirkan ayat-ayat mutashābihāt. Pendekatan ini juga mengkaji bagaimana metode tersebut mempengaruhi pembentukan pengetahuan dan pemahaman dalam konteks keilmuan Islam. Hasil analisis menunjukkan bahwa kaidah Nafiy berperan signifikan dalam menjaga integritas dan konsistensi penafsiran, serta dalam membimbing umat Muslim menuju pemahaman yang lebih mendalam dan akurat terhadap wahyu Ilahi..